Expanding boundaries. Systems thinking in the built environment. Sustainable Built Environment (SBE) Regional Conference Zurich 2016. - (:unkn) unknown (vdf Hochschulverl., 2016)
Consuming over 40% of total primary energy, the built environment is in the centre of worldwide strategies and measures towards a more sustainable future. To provide resilient solutions, a simple optimisation of individual technologies will not be sufficient. In contrast, whole system thinking reveals and exploits connections between parts. Each system interacts with others on different scales (materials, components, buildings, cities) and domains (ecology, economy and social). Whole-system designers optimize the performance of such systems by understanding interconnections and identifying synergies. The more complete the design integration, the better the result. In this book, the reader will find the proceedings of the 2016 Sustainable Built Environment (SBE) Regional Conference in Zurich. Papers have been written by academics and practitioners from all continents to bring forth the latest understanding on systems thinking in the built environment.
Keywords: Bebauung; Stadterneuerung; Stadtgestaltung; Energiesystem; Energieversorgung; Energieplanung; Energietechnologie; Alternativenergie; Gebäudeplanung; Bauplanung; Baumaterial; Bauweise; Innovation; Technische Infrastruktur; Versorgung; Entsorgung; Modellierung; Nachhaltigkeit; Stadtsystem; Smart City; Erneuerbare Energie; Ressourceneffizienz; Ökologisches Bauen; Lebenszykluskosten; Integrierte Planung; Synergie; Smart grid; Smart metering